CLARICE LISPECTOR E O MAL-ESTAR NA LITERATURA - Nolasco, Edgar Cézar (Em Tese, 1998)
Having Clarice Lispector’s Uma aprendizagem ou o livro dos prazeres and Água viva as our object of stuudy, the purpose of this essay is to discuss the process of creations as well as the author’s literary project.